2017
DOI: 10.1016/j.apsusc.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of self-healing superhydrophobic CeO2 surface by electrochemical processes

Abstract: Highlights ・The CeO-coating is formed on Type 304 stainless steel by anodic deposition. ・The hydrophilic CeO 2 surface is transformed to hydrophobic during air exposure. ・Superhydrophobic CeO 2 surface is obtained on hierarchically rough substrate. ・Superhydrophobic CeO 2 surface shows self-healing property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Similar increased hydrocarbon adsorption on CeO 2 surfaces resulting in higher contact angles in comparison to that of other oxide films has been previously reported for ceria pellets. , These results suggest that carbon adsorption on CeO 2 surfaces is relatively spontaneous and favorable, which can be explained by the presence of oxygen vacancies in ceria and hence an increase in the number of adsorption sites . The findings reported in this work are in agreement with previously published studies, which note that CeO 2 is initially hydrophilic but quickly becomes hydrophobic upon atmospheric exposure and the resulting carbon adsorption on the surface. ,,,,, There have been a number of studies, which assigned an intrinsic hydrophobic nature to ceria and other lanthanide oxides. ,,, However, we found that to measure the intrinsic wetting properties of a high-energy surface like ceria, it must undergo a proper cleaning procedure prior to the contact angle measurements. The hydrophobic nature of CeO 2 has typically been observed after the surface was rinsed with organic solvents or water, which we found is not effective for removing carbon contaminants.…”
Section: Resultssupporting
confidence: 91%
“…Similar increased hydrocarbon adsorption on CeO 2 surfaces resulting in higher contact angles in comparison to that of other oxide films has been previously reported for ceria pellets. , These results suggest that carbon adsorption on CeO 2 surfaces is relatively spontaneous and favorable, which can be explained by the presence of oxygen vacancies in ceria and hence an increase in the number of adsorption sites . The findings reported in this work are in agreement with previously published studies, which note that CeO 2 is initially hydrophilic but quickly becomes hydrophobic upon atmospheric exposure and the resulting carbon adsorption on the surface. ,,,,, There have been a number of studies, which assigned an intrinsic hydrophobic nature to ceria and other lanthanide oxides. ,,, However, we found that to measure the intrinsic wetting properties of a high-energy surface like ceria, it must undergo a proper cleaning procedure prior to the contact angle measurements. The hydrophobic nature of CeO 2 has typically been observed after the surface was rinsed with organic solvents or water, which we found is not effective for removing carbon contaminants.…”
Section: Resultssupporting
confidence: 91%
“…The first one is related to the time of saturation for wetting properties. In various works [6]- [9], [18], the period of establishment for the hydrophobic state of CeO2 and other REOs is found in the large range from days to months. Applying the deposition process in a saturated environment allows the completion time to be reduced from days to hours.…”
Section: Methodsmentioning
confidence: 99%
“…Organic surface is usually required to satisfy this criterion, although there are some reports indicating that rare earth oxides exhibit hydrophobicity without any organic coating. [17][18][19] In contrast to the superhydrophobic surfaces, the fabrication of superoleophobic surfaces is rather difficult because of the lower surface tension of oils. The most organic surfaces with -CH 3 , -CH 2 , -CF 2 and -CF 3 outermost groups are oleophilic with static contact angles less than 90° for the low surface tension liquids ( < 30 mN m − 1 ); these organic surfaces are wetted to oils even after surface roughening.…”
Section: Fabrication Of Superoleophobic Surface On Stainless Steel Bymentioning
confidence: 99%